ETHNOBOTANY OF AQUEOUS PLANTS AT NONG HAN KUMPHAWAPI WETLAND, UDORNTHANI, THAILAND: SAVING TRADITIONAL KNOWLEDGE THROUGH LOCAL RESOURCE-BASED ECONOMY - Pagdee, A.; Homchuen, S.; Pornpipat, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
An ethnobotanic study of aquatic plants at Nong Han Kumphawapi—a wetland of international importance, Udornthani, Thailand was conducted from June to August, 2006. Data were collected by in-depth interviews of seven senior villagers and traditional healers, coupled with field and local market surveys. In total, 62 species (33 families) of aquatic plants were reported to be used for subsistence, including food, medicines, household tools, animal feed and community rituals. Edible and medicinal plants are most frequently harvested, accounted for 45% and 26% of all identified species respectively. The family most frequently used is Cyperaceae i.e. Scirpus grossus L.f. and Cyperus corymbosus Hook.f. Key informants reported that ethnobotanic knowledge was passed along through storytellers rather than written documentation. Currently, due to technology development, socio-cultural transformation, access to market goods and nature of knowledge transfer, ethnobotany especially use of medicinal plants is fading away. Hence, loss of potential usefulness is likely even before these species can be studied. Wetland resource management, including detailed assessment of ecosystem status, biodiversity quantities, productivity potential, and sustainable use methods is necessary. Furthermore, local communities need to recognize the importance of ethnobotany and participate in the management. Day-to-day use and value addition of these species need to be promoted, so ethnobotany becomes part of a community economy. This can be seen in Thailand under the national program called “OTOP—One Tambon (an products made from local resources and selects one to generate its economy. administrative level equivalent to sub-district) One Product.” Every Tambon develops its most unique